Weed management strategies in maize (Zea mays): Effect on weed dynamics, productivity and economics of the maize- wheat (Triticum aestivum) cropping system in Indo-gangetic plains - SINGH, ADITYA KUMAR; PARIHAR, C M; JAT, S L; SINGH, BAHADUR; SHARMA, SAVITA (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted to evaluate the efficacy of different herbicidal treatments along with cowpea (Vigna unguiculata (L.) Walp.) as live mulch crop as one of the treatments in preceeding maize (Zea mays L.) and their residual effects on succeeding wheat (Triticum aestivum L.) crop during 2010-11 and 2011-12. In maize field, metribuzin/atrazine was not found effective to control Dactyloctenium colonum, however, application of metribuzin 0.25 kg/ha as pre emergence (PE) followed by one hand weeding at 21 DAS was found most effective in controlling this weed. Metribuzin 0.25 kg/ha as PE + one hand weeding (HW) and maize + cowpea intercropping resulted in significantly lowest weed index which remained at par with atrazine as PE + one HW. However, after pooled analysis of results significantly highest grain yield (6 785 kg/ha) of maize was obtained with two HW, while highest grain yield of succeeding wheat (6 191 kg/ha) was obtained with the preceding effect of maize + cowpea. The highest pooled system productivity as maize equivalent yield (14 136 kg/ha) was obtained with maize + cowpea treatment which remained at par with application of atrazine or metribuzin as PE plus one HW. Significantly highest pooled gross (Rupees 153 864/ha), net (Rupees 101 948/ha) returns and B:C ratio (1.96) were also obtained with maize + cowpea, which remained at par with other tested weed management practices. The results indicate that inclusion of cowpea as cover crop in maize-wheat system will not only increase the profitability but also provide environment friendly option against the use of herbicides for weed management.